Medición y mejoramiento del clima laboral de los departamentos de biblioteca y sistemas del campus Girón de la Universidad Politécnica Salesiana - Zambrano Velasco, Diana Carolina (2017)
The present project arose because of the need to know the perception that the personnel of the technical departments of library and systems of the Salesian Polytechnic University Campus Girón with regard to its working environment in order to be able the generate improvement actions since the work environment influences in performance, behavior and in interpersonal relationships, in addition, because this type of processes that are relevant in every institution has never been executed before. The Salesian Polytechnic University is an institution of higher education focuses on students, teaching staff and administrative, but not provided to the last staff the same opportunities that the rest of employees, that is the reason for which emerged the idea to measure to later improve the working environment of directions of the library and systems, to generate actions with the staff of these departments because that also improve your satisfaction improves attention afforded to them students, also improve the relations between colleagues, the communication and the work in team. It was planned to create an instrument to measure staff satisfaction, using the Likert attitudes scales, in which five aspects or factors to be measured were established and within each aspect three items or specific questions were elaborated, questions were drawn from the needs detected and the reality of the institution.